Exploring the link between parvovirus B19 and encephalitis: a systematic review and comprehensive meta-analysis of molecular and serological evidence - Kashmi Sharma; Rekha Khandia; Rohan Shrivastava; Ram K. Nema; Somesh Mishra; Rupinder K. Kanwar; Ashwin A. Raut; Amit Agrawal; Vandana Gupta; Megha K. Pandey (Virology Journal)
Abstract Encephalitis, a severe brain inflammation, can arise due to various infectious agents, including viruses like Parvovirus B19 (B19V). Previously linked to mild neonatal and young one’s illnesses and some haematological diseases, recent evidence associates B19V with encephalitis, with no clear prevalence and mechanisms in place. This systematic review and meta-analysis aim to determine the prevalence of B19V in cases of encephalitis, exploring variations associated with diagnostic approaches, and identifying gaps in existing research to enhance clinical comprehension and diagnostic methods. An extensive search (1994–2024) was performed through PubMed, Scopus, ScienceDirect, and Cochrane databases for research and epidemiological investigations related to B19V in cases of encephalitis. Inclusion criteria focused on studies that verified B19V using molecular (PCR, NGS) or serological (IgM/IgG) techniques in cerebrospinal fluid or serum. Data analysis was done to pool the prevalence data of included studies using a random-effects model. Heterogeneity was evaluated using I2 statistics. Sensitivity and meta-regression analyses were conducted to evaluate variability and the effects of moderators. A total of fourteen studies involving 3,135 encephalitis patients resulted in a combined prevalence of 3% (95% CI: 2–4%). Studies using PCR indicated a greater prevalence (3%) in comparison to ELISA (1%) and NGS (2%). A moderate level of heterogeneity (I2 = 57.4%) was attributed to the variability in diagnostic methods and geographic distribution. Sensitivity analyses validated strong estimates, while meta-regression revealed country as a key moderator accounting for heterogeneity. Publication bias was modest. The research indicates that B19V may be involved in certain encephalitis instances, with an overall prevalence of 3%. The differences observed in the studies emphasize the need for standardized diagnostic procedures and more extensive multicentric epidemiological research.